Clinical profile and predictors of positivity of acetylcholine test in patients with angina and no obstructive coronary artery disease. Results of a multi-center mediterranean registry. (25th November 2020) - Grigorian, L; Gutierrez, E; Oteo, J.F; Abdul-Jawad, O; Amat Santos, I; Gutierrez Barrios, A; Fernandez Cisnal, A; Jimenez Mazuecos, J; Roa, J; Vazquez, M.E; Sanz, R; Diez-Delhoyo, F; et al.
Abstract: Background: Coronary endothelial dysfunction and vasospasm are potential causes of ischemia in no obstructive coronary disease (INOCA) and are now known to be associated with an increased risk of major cardiovascular events (MACE) and impaired quality of life. The recent guidelines recommend the use of intracoronary acetylcholine to unravel the underlying pathophysiology of INOCA, by identifying those with endothelial dysfunction, and to guide future treatment in these patients. Objective: To evaluate the clinical profile and prevalence of endothelial dysfunction in patients with INOCA, and to identify the predictors of positivity of the acetylcholine test. Methods: A total of 358 patients with INOCA were prospectively enrolled in a multicenter observational study. Coronary angiography and acetylcholine test were performed according to clinical indications in all included patients. Patients were followed-up for 1-year for MACE and clinical reevaluation of symptoms. Results: Patients' mean age was 60.6±13.5 y.o. and 58.7% were females, with no previous history of coronary heart disease in 76% of cases. Regarding clinical presentation, 56.9% had angina at rest, 59.9% exertional angina, and 29.5% dyspnea. In 39% the EKG was abnormal, and in 10.9% there was a troponin rise. Coronary endothelial dysfunction –defined as a vasoconstriction over 30%– was observed in 129 (36%) patients, and severe vasoconstriction (>70%) in 75 (21%). Of positive cases, 47 (36%) focal vasoconstriction, and 90 (70%) diffuse. On follow-up, patients with a positive Ach test were treated differently, with a lower prescription of betablockers (12% vs. 24%, p=0.01) and a higher use of vasodilators (47% vs. 28.5%, p=0.001). Guidelines-recommended optimal treatment was prescribed to 39.2% of patients with a positive acetylcholine test. Patients with positive acetylcholine test were more prone to having worsening angina (25.6% vs. 12.8%, p<0.01) and minimal exertion angina (40% vs. 26.7%, p=0.03) on follow-up. Multivariable regression analysis showed that acetylcholine test positivity was predicted by the presence of diabetes (OR 1.7, p=0.04), exertional angina (OR 1.2, p=0.04), coronary atherosclerosis (OR 1.8, p=0.02) and coronary milking (OR 2.6, p=0.04). Conclusions: Endothelial dysfunction detected by acetylcholine test was present in one third of patients with INOCA and was associated with more severe and worsening symptoms. Although Ach test positivity influenced the pharmacological treatment at discharge, a large room for optimization still remained. Funding Acknowledgement: Type of funding source: None